(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2025)
This study examines the application of the Six Sigma methodology to improve production process quality in the plastic packaging industry, a vital sector in Libya due to its role in industrial packaging and cost efficiency. The research aims to reduce defect rates, minimize waste, and enhance operational performance in manufacturing environments that rely heavily on automated machinery without structured improvement frameworks. The DMAIC approach was applied to an injection molding machine at Al-Yaqout Plastic Industries Factory to identify recurring defects, analyze their root causes, and evaluate the sustainability of improvements. The study employed descriptive and experimental methods, collecting production data over six months. Defect rates were analyzed, the process sigma level was calculated, and defects were examined in relation to operating conditions, power supply stability, start-up phases, and human intervention. The results showed that the average process performance reached 3.818 sigma, indicating a moderate to good level with clear improvement potential. The most critical defects involved label distortion and container frame deformation, primarily caused by unstable power supply, inadequate preventive maintenance, and temperature fluctuations during start-up. After implementing corrective actions, the defect rate decreased by approximately 27%, confirming the effectiveness of Six Sigma in enhancing production quality and operational stability.